Família como rede de apoio para a prevenção de transtornos mentais em grávidas e puérperas - Oliveira, Mariana Gomes Lapa de (2023)
Throughout the female life cycle there are moments of significant biopsychosocial changes; the pregnancy-puerperal period is one of them. It has the potential to develop transformations that lead to the need for better understanding for the identification of factors that facilitate this process experienced by the woman. Objective: To understand the importance that nuclear and extended families have for women in the gravidic-puerperal cycle, as a support network for the prevention of disorders and possible emotional changes. Method: This is a descriptive, cross-sectional research with comparisons of variables, intra and intergroups. It uses the snowball sampling technique to recruit women from the population living in small and medium-sized cities in the interior of the state of São Paulo. The instrument used for data collection was a semi-structured interview, comprising sociodemographic data, characteristics related to pregnancy and puerperium, mental health (anxiety, depression and stress) and family social support network. The answers were collected using the Google Forms tool, sent to pregnant and postpartum women using the WhatsApp. After collection, the information was submitted to the Quantitative-Interpretative System, described by Sigolo and Biasoli-Alves (1998) and grouped and compared, according to their similarities by non-parametric statistical analysis with a significance index of 0.05. Conclusion: There are several protective factors for the mental health of women experiencing the gravidic-puerperal cycle, such as favorable socioeconomic issues, pregnancy planning, high educational level and the social support received. It can be observed the influence of the family (nuclear and extended) as a support network for pregnant and postpartum women regarding the possible prevention of mental disorders in this population. Further research is recommended in this area.